1999
DOI: 10.1034/j.1399-6576.1999.430601.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of stress in anaesthetists’ health and well‐being

Abstract: Stress is an inevitable part of our personal and professional lives. When poorly managed, stress will accumulate to levels that become injurious to our health and well-being. Burnout is one such consequence. However, because stress is an active process, with the proper knowledge and skills, we can learn to better manage and control its level of intensity. This paper examines the stress cycle and especially those aspects that are unique to the practice of medicine and anaesthesia. Sleep deprivation and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 49 publications
4
84
0
5
Order By: Relevance
“…Various studies 3−8 have identified anaesthetists as being at high risk for burnout. The increased rate of suicide, twice as high as for the general public, 9 and the elevated incidence of chemical dependence 6,10 in anaesthetists are major causes for concern. Added to this, several studies have found burnout to affect younger and more inexperienced doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies 3−8 have identified anaesthetists as being at high risk for burnout. The increased rate of suicide, twice as high as for the general public, 9 and the elevated incidence of chemical dependence 6,10 in anaesthetists are major causes for concern. Added to this, several studies have found burnout to affect younger and more inexperienced doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Regional or perhaps hospital variation may exist and it would be useful to know what the set standard is and how many epidurals the respondents initially sited under direct supervision. Workplace stress amongst anaesthetists is frequently reported (Larsson, Rosenqvist, Holmstrom, 2006; Jackson, 1999; Houston, Allt, 1999) [14][15][16]. The survey findings are significant and may translate into the need for more direct supervision or a comprehensive training program, including the use of simulation.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of health conditions of workers performed by the Ministry of Health, Labor, and Welfare has shown that the stress of workers in Japan has increased, and that the percentage of workers with "severe anxiety, troubles, and stress in their work and occupational life" increased from 50.6% in 1982 to 61.5% in 2002. In overseas reports, anesthesiologists have also been found to have more stress than other physicians [12,13], with the reasons for such severe stress including less satisfaction in their work, long working hours, on-call work, fear of court cases, and problems with relationships with physicians in other departments [14][15][16]. An investigation performed by the American Society of Anesthesiologists in 1991 indicated that the greatest stress was caused by on-call work at night, in addition to stress due to the requirement for anesthesia for patients at high risk, work responsibilities, and a heavy workload [17].…”
Section: Discussionmentioning
confidence: 99%